Rhynchophylline was exported to cerebral spinal fluid and systemic circulation after intracerebroventricular administration to rats detected by ultra‐high performance liquid chromatography coupled with mass spectrometry. Issue 5 (24th February 2020) - Xu, Xiangting; Luo, Shaozhong; Li, Meihong; Song, Jingfeng; Wang, Wei
Abstract: An ultra‐high performance liquid chromatography coupled with mass spectrometry method was developed and validated to determine rhynchophylline in the rat brain and spinal cord, cerebral spinal fluid, and systemic circulation after a single intracerebroventricular administration. The in vivo dynamics of rhynchophylline in rat central nervous system was described through comparison its distribution in systemic circulation. After administration of 100.9  μ g/kg 4 h, rhynchophylline 44.6% stayed in brain and spinal cord of 1.2 g, 7.24% in cerebral spinal fluid of 400 μ L, and 43.3% in plasma of 8.5 mL, respectively. The mean linearity coefficient was of 0.9995. Accuracy varied from 98.66 to 101.78%, with precision expressed as RSD from 1.15 to 3.13%. The recoveries ranged from 95.78 to 101.92%. This is the first time to present an efficient and effective quantification method for rhynchophylline in the cerebral spinal fluid, brain and spinal cord of rats, which was supposed to have pharmacological effects in the treatment of brain diseases.